AD, Volume 22, n° 1, 1997 - Full Issue - Journal System (Africa Development, 1997)
Contents Introduction Ayesha lmam ............................. 5 Bitches at the Academy: Gender and Academic Freedom at the African University Sylvia Tamale and J. Oloka-Onyango ...................... 13 School Participation by Gender: Implications for Occupational Activities in Kenya Ruth N. Otunga .............................. 39 Etre une femme intellectuelle en Afrique: de la persistance des stéréotypes culturels sexistes C. Zoe Naré ................................... 65 Reproductive Health and Rights: The Case of Northern Nigerian Hausa Women Hajara Usman ................................ 79 Culture, Gender, and Development Theories in Africa Sophie B. Oluwole ........................ 95 Politics and Gender Relations in Kenya: A Historical Perspective Hannington Ochwada .................123 The State, Women and Démocratisation in Africa: The Nigerian Experience (1987-1993) Pat Williams .................................141 Book Reviews Rose W. Gaciabu, De-feminization of Poverty in Africa: Are We Keeping the Promise? Nairobi, Catholic University of Eastern Africa, 1996,43p. Hannington Ochwada .................183 Maria Nzomo, Women in Top Management in Kenya, Nairobi, African Association for Public Administration and Management, 1995, iii+91p Hannington Ochwada ................ 187 Publications Received and Acquired ................. 191 Index to Africa Development Vol XXI, 1996 ........ 195